1997
DOI: 10.1111/j.1365-2621.1997.tb04015.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins Applied to Food Packaging Materials to Inhibit Listeria monocytogenes on Meats

Abstract: Bacteriocins in powders were produced from milk-based media and applied to food packaging films. Nisin and pediocin ''powders'' were retained in casings during dialysis. Antilisterial casings were prepared by internal coating with pediocin. Antilisterial activity applied in powdered form was retained during processing and retained on contact food packaging surfaces. Pediocin powder was applied to plastic packaging bags at 7.75 µg/cm 2 . Meats and poultry samples were inoculated with Listeria monocytogenes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(96 citation statements)
references
References 16 publications
3
91
0
2
Order By: Relevance
“…Nisin Z causes an immediate loss of cell K ϩ , phosphate, and ATP in L. monocytogenes, suggesting the unselectivity of these pores (2). In addition, the bactericidal effect of nisin through pore formation has been found to be an energy-and transmembrane electrical potential-dependent process in the absence of lipid II (47,54,62). When lipid II is available, nisin can disturb the barrier function of membrane at nanomolar concentrations, compared to micromolar range without lipid II (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nisin Z causes an immediate loss of cell K ϩ , phosphate, and ATP in L. monocytogenes, suggesting the unselectivity of these pores (2). In addition, the bactericidal effect of nisin through pore formation has been found to be an energy-and transmembrane electrical potential-dependent process in the absence of lipid II (47,54,62). When lipid II is available, nisin can disturb the barrier function of membrane at nanomolar concentrations, compared to micromolar range without lipid II (62).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, immobilization of nisin Z on liposome membranes appeared to protect its activity and improve its availability and distribution in the cheese matrix. Adsorption of bacteriocins to various surfaces with retention of activity may be successfully achieved (10,11,21,47). Membrane-immobilized nisin or surfaces could provide several advantages as a nisin delivery system, such as reducing the amount of nisin that would be used and improving its stability (20,58).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, niacin give good results in decontaminating meat surface when applied in combination with alginate-based edible coatings. Accordingly in a study, Ming et al (1997) reported that sausages can be preserved by treating their inner surface with bacteriocins. They also applied niacin and pediocin to inner side of packaging materials and noticed a significant reduction for Listeria monocytogenes in breast turkey meat, ham and beef under refrigerated storage.…”
Section: Bacteriocinsmentioning
confidence: 99%
“…Another investigated bacteriocin was pediocin which was introduced into the cellulose fi lm. The foil with its addition was demonstrated to completely inhibit the growth of L. monocytogenes bacteria [Ming et al, 1997]. Equally promising results were achieved in a study conducted with a pullulan fi lm enriched with bacteriocin, namely with sakacin A.…”
Section: Antimicrobial Substances Most Frequently Introduced Into Filmentioning
confidence: 68%